The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3168/jds.2020-19200
|View full text |Cite
|
Sign up to set email alerts
|

Associations between body condition score, locomotion score, and sensor-based time budgets of dairy cattle during the dry period and early lactation

Abstract: Lameness, one of the most important disorders in the dairy industry, is related to postpartum diseases and has an effect on dairy cow welfare, leading to changes in cows' daily behavioral variables. This study quantified the effect of lameness on the daily time budget of dairy cows in the transition period. In total, 784 multiparous dairy cows from 8 commercial Dutch dairy farms were visually scored on their locomotion (score of 1-5) and body condition (score of 1-5). Each cow was scored in the early and late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…The farms contributing to this study can be considered representative of the modern Dutch dairy industry. For further details of the farms, see Table 1 and Hut et al (2021). Farms differed in the exact times of milking and fresh feed delivery, as well as in the exact ration composition.…”
Section: Farms Animals and Sensorsmentioning
confidence: 99%
“…The farms contributing to this study can be considered representative of the modern Dutch dairy industry. For further details of the farms, see Table 1 and Hut et al (2021). Farms differed in the exact times of milking and fresh feed delivery, as well as in the exact ration composition.…”
Section: Farms Animals and Sensorsmentioning
confidence: 99%
“…Various studies (Norring et al, 2014;Weigele et al, 2018) have shown less feeding time for lame cows per day and this indicator would further deteriorate with the progression of lameness (Norring et al, 2014). Hut et al (2021) found a decrease in daily eating time of 20 min for moderately and 40 min for severely lame cows compared to healthy ones. In the study of Almeida et al (2008), in addition to shorter eating time, lame cows showed almost 30% decreased rumination time, although this finding was not consistent across studies (Hut et al, 2021;Weigele et al, 2018).…”
Section: Lameness and Behavioural Changesmentioning
confidence: 99%
“…All dairy cows on the 8 commercial dairy farms in The Netherlands included in this study were equipped with 2 types of sensors. Details of these farms, with an average herd size of 140 cows, are described in Table 1 and in our previous publication on lameness [26]. To monitor feeding behavior (eating time and rumination time), commercially available "Nedap Smarttag Neck" sensors (Nedap, Groenlo, The Netherlands) were attached to the neck collar of each cow and the commercially available "Nedap Smarttag Leg" sensors were attached to one of the front legs of each cow, to monitor walking (walking time and standing time) and lying behavior (lying time).…”
Section: Farms Animals and Sensorsmentioning
confidence: 99%
“…In total, 1074 cows with 3201 lactations were available in this study. The use of such sensors in a commercial dairy herd is not considered an animal experiment under Dutch law, hence no formal ethical approval was needed (see also [26]). The number of cows per sensor based behavioral parameter is presented in Fig 1 . For visualization purposes, farms were grouped by type of milking system (AMS, N = 3 / CMS, N = 5) where cows on CMS farms also had pasture access during parts of spring, summer and autumn for at least 120 days/year for at least 6h/day as a part of a subsidized Dutch system to stimulate pasture access for dairy cows.…”
Section: Farms Animals and Sensorsmentioning
confidence: 99%